Effectiveness of the Construction Services Outsourcing. Case of the Specialized Construction Company - Mariusz Włodarz (Contemporary Economics)
The article is the case of outsource the construction services made by Gazbud Ltd., one of construction firm, which realized its activity on the south of Poland. Main goal of the publication is concentrated on the problem, how it is possible to measure and control outsourcing effectiveness.